2016
DOI: 10.4103/2231-0762.195514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of education based on the theory of planned behavior on adoption of oral health behaviors of pregnant women referred to health centers of Birjand in 2016

Abstract: Objective:Oral health of pregnant women is very important because of the adverse effects of pregnancy on the oral hard and soft tissues and vice versa. The aim of this study was to evaluate the effect of education on oral health behaviors of pregnant women based on the theory of planned behavior in Birjand.Materials and Methods:This quasi-experimental study was carried out among 150 pregnant women admitted to health centers, who were selected using simple sampling (75 females in each case and control group). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 16 publications
(16 reference statements)
5
20
0
Order By: Relevance
“…57 The results of the Daniel study revealed that attitude was the strongest predictor of brushing behaviour, followed by oral health knowledge, perceived behavioural control and subjective norms. 58 According to Ebrahimpour et al, 32 after the intervention based on TPB, the mean scores of knowledge, attitude, perceived behavioural control, subjective norms and behavioural intention in the intervention group showed a significant increase compared to the control group (P ≤ 0.05). Similarly the results of Buunk-Werkhoven showed that the TPB variables emerged as significant predictors of oral health behaviour.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…57 The results of the Daniel study revealed that attitude was the strongest predictor of brushing behaviour, followed by oral health knowledge, perceived behavioural control and subjective norms. 58 According to Ebrahimpour et al, 32 after the intervention based on TPB, the mean scores of knowledge, attitude, perceived behavioural control, subjective norms and behavioural intention in the intervention group showed a significant increase compared to the control group (P ≤ 0.05). Similarly the results of Buunk-Werkhoven showed that the TPB variables emerged as significant predictors of oral health behaviour.…”
Section: Discussionmentioning
confidence: 95%
“…49 The effect of this theory after six months of follow-up was the lowest difference observed between the case and control groups. 58 According to Ebrahimpour et al, 32 The use of the TPB framework permitted health educators to design interventions and identify factors associated with evidencebased practice on oral health. These findings of the current study are F I G U R E 4 Forrest plot of theory of planned behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the students' behavioral intention scores increased signi cantly after the educational intervention. In the study by Ebrahimipour et al oral and dental health education based on the theory of planned behavior increased the behavioral intention score of pregnant women from 17.3 ± 2.5 to 21.4 ± 2 [40]. Behavioral preferences were the major effective variables in displaying brushing behavior, so it is suggested that parents consider children's behavioral preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Most pregnant women in this study experienced an increase in perceived knowledge about normal birth, cesarean, and EBP after participating in the SoB intervention. Prior studies that evaluated the impact of a health education intervention on women's preference, knowledge, skills, and behavior found that culturally appropriate maternity care has positive effects on increasing knowledge, stronger attitude, perceived behavior control, and the use of skilled maternity care among women (10,63,64). Recent findings from the "Lancet Series of Optimizing Caesarean Section Use" also showed that non-clinical health-care interventions to reduce unnecessary C-sections are most effective when prioritizing human relationships, promoting respectful and collaborative care, and addressing women's beliefs and attitudes (58).…”
Section: The Sob Intervention's Impact On Women's Perceived Knowledgementioning
confidence: 99%